Pelatihan Pembuatan PMT Berbasis Daun Kelor dalam Upaya Pencegahan Stunting di Desa Jati - Mangasa Barakel; Adinan Rizfauzi; Revinta Nur Aulia Rochly (Universitas Negeri Semarang, 2025)
Stunting is a serious issue in child growth in Indonesia, as it has long-term negative impacts. Many efforts have been made to prevent and address stunting, one of which is the provision of supplementary food (PMT). In Jati Village, Jaten District, Karanganyar Regency, for example, efforts have begun to prevent stunting by utilizing the nutritional content of moringa leaves as the base ingredient for making PMT, in addition to regularly conducting monthly posyandu (integrated health posts) activities. This article is written using an observational method. The UNNES GIAT 7 Jati Village team has also been involved in socializing the practice of making PMT menus with moringa leaves as the base ingredient alongside the posyandu cadres of Banaran Hamlet, Jati Village. This activity is one of the efforts by the UNNES GIAT 7 Jati Village team to provide understanding to posyandu cadres in preventing stunting.